2021
DOI: 10.1007/s13730-021-00612-y
|View full text |Cite
|
Sign up to set email alerts
|

LMX1B-associated nephropathy that showed myelin figures on electron microscopy

Abstract: The mutation of LIM homeodomain transcription factor LMX1B gene leads to nail-patella syndrome (NPS), which is characterized by dysplastic nails, hypoplastic patellae, iliac horns and nephropathy. The characteristic renal histological finding of NPS nephropathy is irregular thickening of the glomerular basement membrane with patchy lucent areas, including deposits of bundles of type III collagen fibrils revealed by electron microscopy (EM). Fabry disease is a lysosomal storage disorder caused by a deficiency o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Genetic testing has revealed that all patients possess LMX1B (c.737G > A, p.R246Q) mutations, leading to their eventual diagnosis of NPLRD. [ 13 , 14 , 17 ] This discovery enhances our comprehension of kidney biopsy in NPLRD. In our reported renal disease cohort, all 3 patients who underwent kidney biopsies exhibited ischemic renal impairment, and immunofluorescence shows negative antibodies in the mesangial area of kidney biopsy.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Genetic testing has revealed that all patients possess LMX1B (c.737G > A, p.R246Q) mutations, leading to their eventual diagnosis of NPLRD. [ 13 , 14 , 17 ] This discovery enhances our comprehension of kidney biopsy in NPLRD. In our reported renal disease cohort, all 3 patients who underwent kidney biopsies exhibited ischemic renal impairment, and immunofluorescence shows negative antibodies in the mesangial area of kidney biopsy.…”
Section: Discussionmentioning
confidence: 82%
“…[8,9] In recent years, NPLRD without extrarenal manifestations caused by LMX1B gene mutation has aroused the interest of workers. [10][11][12][13][14][15][16][17][18][19][20] NPLRD caused by LMX1B mutations lacks extra-renal manifestations, it is often misdiagnosed due to nonspecific symptoms and renal pathology. This study presents a comprehensive analysis of a large three-generation Chinese family exhibiting an autosomal dominant pattern of chronic kidney disease.…”
Section: Discussionmentioning
confidence: 99%
“…This is an autosomal-dominant disease characterized by dysplastic nails and elbows, hypoplastic or absent patellae, iliac horns, and nephropathy ( 55 ). LMX1B mutants without extrarenal manifestations are recognized as LMX1B-associated nephropathy ( 56 , 57 ). LMX1B contains two LIM-domains (LIM-A and LIM-B), which are involved in protein-protein interactions, and a homeodomain, which interacts with specific DNA elements in target genes ( 58 ).…”
Section: Transcription Factors Of Podocytes Related To Fsgsmentioning
confidence: 99%
“…Immunofluorescence microscopy yields negative or non-specific findings, such as slight granular deposits of C3 in the mesangium. Specific immunohistochemical analyses show that the fibrillar material present within the GBM (and occasionally the mesangial matrix) is type III collagen[ 78 - 82 ]. The histological phenotype of LAN is expanding, as heterozygous mutations in the LMXIβ gene have been reported in patients with autosomal dominant FSGS without ultrastructural abnormalities of the GBM and in families with FSGS and myelin figures and zebra bodies (electron-dense multilamellar inclusions) in podocytes, mesangial cells, and tubular epithelium.…”
Section: Normal Composition Of the Human Gbm And Mesangial Matrixmentioning
confidence: 99%
“…Therefore, LMX1β pathogenic variants should be ruled out as a potential cause of autosomal dominant kidney disease, sporadic and hereditary forms of FSGS, and steroid-resistant nephrotic syndrome, regardless of extrarenal manifestations. In addition, the presence of myelin figures or zebra bodies may hint toward LAN diagnosis in patients free of lysosomal storage disorders or drug-induced phospholipidosis, although the mechanism underlying the appearance of these structures in LAN is unclear[ 80 , 82 , 83 ].…”
Section: Normal Composition Of the Human Gbm And Mesangial Matrixmentioning
confidence: 99%